THE PLATED BAYONET - A NEW INSTRUMENT TO FACILITATE SURGERY FOR INTRAAXIAL NEOPLASMS OF THE SPINAL-CORD AND BRAIN-STEM - TECHNICAL NOTE - (:unkn) unknown (AMER ASSOC NEUROLOGICAL SURGEONS, 1993)
A new instrument for use in surgically treating intra-axial neoplasms of the spinal cord and brain stem is described. The plated bayonet allows neoplastic tissue in the spinal cord to be separated from functioning neural elements without perforating the adjacent spinal cord. In addition, the plated bayonet facilitates exposure through the very small incision necessary to remove tumors of the brain stem without damaging cranial nerves or other vital structures.
Keywords: SPINAL CORD NEOPLASM; BRAIN-STEM NEOPLASM; CAUDA EQUINA TUMOR; INSTRUMENTATION